Electrophysiological Study of Femoral Nerve Function After a Continuous Femoral Nerve Block for Anterior Cruciate Ligament Reconstruction: A Randomized, Controlled Single-Blind Trial. (March 2017) - Stebler, Kevin; Martin, Robin; Kirkham, Kyle Robert; Küntzer, Thierry; Bathory, Istvan; Albrecht, Eric
Background: A continuous femoral nerve block (CFNB) is an effective analgesic treatment after anterior cruciate ligament (ACL) reconstruction but may result in transient femoral nerve injuries and quadriceps muscle weakness, which in turn contribute to worsened functional outcomes. Purpose: To compare electrophysiological criteria of a femoral nerve injury as well as functional and pain-related outcomes after ACL reconstruction when analgesia was provided by a CFNB or intravenous patient-controlled analgesic of morphine (IV PCA). Study Design: Randomized controlled clinical trial; Level of evidence, 1. Methods: A total of 74 patients scheduled for ACL reconstruction were randomized to receive a CFNB before surgery, followed by a ropivacaine infusion for 2 days and oxycodone, or IV PCA. The primary outcome was the rate of femoral nerve injuries at 4 weeks postoperatively, defined as a reduction of the compound muscle action potential (CMAP) area from the vastus medialis muscle after supramaximal femoral nerve stimulation at the groin, associated with an absent H-reflex of the femoral nerve and signs of vastus medialis muscle denervation. Secondary functional outcomes were quadriceps muscle strength, active flexion range, and distance walked, as measured on postoperative days 1 and 2. Secondary pain-related outcomes were IV morphine consumption and pain scores at rest and on movement in phase 1 recovery and on postoperative days 1 and 2. Results: No patients met the electrophysiological criteria of a femoral nerve injury. The mean CMAP area at 4 weeks was equivalent in both the CFNB and IV PCA groups (47 ± 16 mV·ms and 51 ± 13 mV·ms, respectively; P = .50). While no differences were detected in functional outcomes or pain scores, the consumption of an IV morphine equivalent was reduced by the administration of a CFNB in phase 1 recovery (6 ± 5 mg and 13 ± 7 mg, respectively; P = .0003), on postoperative day 1 (6 ± 7 mg and 19 ± 17 mg, respectively; P = .0005), and on postoperative day 2 (11 ± 10 mg and 19 ± 17 mg, respectively; P = .03) compared with an IV PCA. Conclusion: Despite prior contrary reports, a CFNB did not result in femoral nerve injuries or worsened functional outcomes after ACL reconstruction. The improvement of analgesia with a CFNB was only marginal and not clinically relevant beyond 24 hours. Registration: NCT01321138 (ClinicalTrials.gov identifier).